REVIEW OF THE NATIONAL LEGAL SYSTEM ON THE MECHANISM OF RESOLVING CRIMINAL ACTS OF REGIONAL HEAD ELECTIONS BASED ON INTER-AGENCY AUTHORITY - Teguh Syuhada Lubis, Mhd (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
An election crime can be formulated as any action/deed (active/passive) that violates the provisions in the stages of election administration and is threatened with criminal sanctions. Many people claim that at this time the election. This research uses normative legal research, with a research approach to legal systematics. Forms of normative legal research. The data of this study consisted of secondary data. Secondary data is data obtained from relevant literature studies in this study. Secondary data is "data sourced from library research related to publications, namely library data listed in official documents. The role of law enforcement agencies with Bawaslu in handling criminal acts of regional head elections in Indonesia is based on the provisions of Article 146 of Law Number 6 of 2020 concerning the Election of Governors, Regents and Mayors, which describes the cooperation between institutions in handling them, namely Bawaslu, the Police and the Attorney General's Office. . The application of criminal sanctions for perpetrators of the General Election of Regional Heads must first meet the criminal elements contained in each criminal article, namely those in Article 177 to Article 198A of Law Number 6 of 2020 concerning the Election of Governors, Regents, and Mayor. After the elements of the article are fulfilled, the perpetrator can be charged with sanctions or criminal responsibility. The national legal system in viewing the inter-institutional authority in the settlement of criminal acts of regional head elections recognizes the position and role of Bawaslu and its staff, namely by forwarding reports of alleged criminal acts that have been studied and proven to be true to the state police of the Republic of Indonesia.